TOOL WEAR MEASUREMENT AFTER MILLING OF ALUMINUM ALLOY USING COMBINED ROUGHNESS AND CONTOUR DEVICE - Jakub MATUSZAK (Applied Computer Science, 2015)
During separation of work surface in machining process and transforming it into chips, tool remains in constant contact with the workpiece. During this contact, there are a series of phenomena leading to the tool wear. Tool wear monitoring, and determination of tool life which is a signal to replace the tool with a new one, is important to ensure the continuity of production process in any company where elements are produced by machining. The article presents the results of tool wear measurement after milling of AlSi10Mg aluminum alloy using combined roughness and contour device.